Hollow Mesoporous Fe2O3 Nanospindles/CNTs Composite: An Efficient Catalyst for High-Performance Li-O2 Batteries - Xue, Hairong; Ma, Yiou; Wang, Tao; Gong, Hao; Gao, Bin; Fan, Xiaoli; Yan, Juanjuan; Meng, Xianguang; Zhang, Songtao; He, Jianping (Frontiers in Chemistry, 2019)
The design of mesoporous or hollow transition metal oxide/carbon hybrid catalysts is very important for rechargeable Li-O2 batteries. Here, spindle-like Fe2O3 with hollow mesoporous structure on CNTs backbones (Fe2O3-HMNS@CNT) are prepared by a facile hydrolysis process combined with low temperature calcination. Within this hybrid structure, the hollow interior and mesoporous shell of the Fe2O3 nanospindles provide high specific surface area and abundant catalytical active sites, which is also beneficial to facilitating the electrolyte infiltration and oxygen diffusion. Furthermore, the crisscrossed CNTs form a three-dimensional (3D) conductive network to accelerate and stabilize the electron transport, which leads to the decreasing internal resistance of electrode. As a cathodic catalyst for Li-O2 batteries, the Fe2O3-HMNS@CNT composite exhibits high specific capacity and excellent cycling stability (more than 100 cycles).